The Impact of Genetic and Acquired Risk Factors on Thromboembolic Events: A Retrospective Study - Rapino, Luca; Stefanski, Ana-Luisa; Dörner, Thomas (Hämostaseologie, 2025)
This study, involving a cohort of 980 patients with arterial and/or venous events, evaluated the relative importance of genetic and traditional risk factors using a machine learning model approach. The analysis revealed that conventional risk factors—such as age, gender, tobacco use, obesity—and acquired thrombophilia (most prominently antiphospholipid syndrome [APS]) outperformed any genetic risk variants analyzed. Of note, the presence of heterozygous FVL mutations was associated with a reduced arterial risk, whereas carriers of heterozygous factor VII activation protease (FSAP) mutations had a lower risk of venous events.Thus, by employing diverse statistical approaches, the study showed that acquired risk factors exert the most substantial impact on the development of thrombotic events, except for the well-known role of FVL mutations in venous events.
Keywords: thrombophilia; gene mutations; risk factors; antiphospholipid syndrome